4(4r+18)+6(r-4)=6r

Simple and best practice solution for 4(4r+18)+6(r-4)=6r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4r+18)+6(r-4)=6r equation:



4(4r+18)+6(r-4)=6r
We move all terms to the left:
4(4r+18)+6(r-4)-(6r)=0
We add all the numbers together, and all the variables
-6r+4(4r+18)+6(r-4)=0
We multiply parentheses
-6r+16r+6r+72-24=0
We add all the numbers together, and all the variables
16r+48=0
We move all terms containing r to the left, all other terms to the right
16r=-48
r=-48/16
r=-3

See similar equations:

| 8(-a+4)=-6-8+8a | | 4=3x=8-4x | | 7.7x-15.7=22.8 | | 1/4x-6=3/4x-12 | | 13h-14=-4+15h | | -8x+14=5x-12 | | 2x–3=5x–4 | | x+3=−x−3x= | | 2(4x+2)=6(x-2) | | 8x-5=-24 | | -4x-10=20 | | 2+3x=4-9x | | 5(x+3)+9=3(x-3)+6 | | 10/12=8/k | | 28=5x+3(x-2)=21 | | -6(y+15)=-3+6 | | 2(2x+6)+8=32 | | 20a+19=8(2a+4)+4a-8 | | 72+10x=117 | | -19b-4=14+b-18b | | 10-10f=-3-11f | | 14x-162=62 | | 3k+5+5=13 | | -7x+3=3x+39 | | -60=4(8x+9) | | -15-4y=12 | | 10x-3=4x+55 | | 2.2x-15.8=4 | | 7p+11=-2p+4(-p-7) | | 4.47(t-17)+2.7=11.64 | | 4m-6=2m+6 | | -3(b+2)+9(b+2)+4(b+2)=-30 |

Equations solver categories